Using Behavior Change Theory to Understand How to Support Screening for Traumatic Brain Injuries Among Women Who Have Experienced Intimate Partner Violence - Blake Nicol; Paul van Donkelaar; Karen Mason; Heather Gainforth (Mary Ann Liebert, 2021)
Background: Women who experience intimate partner violence (IPV) are at a high risk for traumatic brain injuries (TBIs). Women's shelters may be an ideal location for TBI screening. Behavior change theory can help understand factors that influence screening at women's shelters and develop interventions to promote screening. Objective: To use behavior change theory to understand the local context of women's shelters, factors influencing screening for TBIs among staff who work at women's shelters, and co-develop intervention recommendations to promote screening of TBIs at women's shelters. Methods: The research was conducted in three phases in partnership with the Kelowna Women's Shelter. In phase 1, participants (staff at women's shelters across Canada) completed an online survey that assessed their current TBI screening behaviors, knowledge of TBIs, and factors influencing screening. In phase 2, participants (staff at women's shelters in the Okanagan) completed an interview regarding the factors that influence screening for TBIs. In both phases, factors were analyzed using the Theoretical Domains Framework. In phase 3, intervention recommendations were co-developed using the Behavior Change Wheel. Results: In phase 1, findings indicate that participants (n?=?150) lack skills (mean?=?2.1, standard deviation [SD]?=?1.9) and knowledge (mean?=?2.9, SD?=?2.2) with regard to screening and are nervous to screen (mean?=?3.0, SD?=?2.4) for TBIs. In phase 2, 194 barriers to screening for TBI were extracted from 10 interviews with staff members. Prominent domains included knowledge (37%), beliefs about capabilities (16%), and environmental context and resources (15%). Finally, in phase 3, five intervention recommendations were co-developed for interventions aiming to promote TBI screening in women's shelters. Conclusions: This thesis was the first theory-based study to develop intervention recommendations for promoting screening of TBIs at women's shelters. The recommendations have the potential to increase TBI screening at women's shelters ultimately improving the quality of life of women who have experienced a TBI from IPV.